(untitled) (Environment & Health, 2015)
State of the problem. Negative role of industrial noise in the development of professional hearing loss no doubt, but the mechanism of its action on the human organism is very complex and not fully understood, while many authors pay much attention to the vascular factor role in the development of sensorineural hearing loss. The objective was to conduct a comparative analysis of the results of research on auditory function, qualitative and quantitative indicators of rheoencephalography in the coal industry from different occupational groups workers with the sensorineural hearing loss and health normal-hearing control subjects with regard to noise load. Materials and methods. The rheoencephalography was performed in 50 workers. The control group — 15 healthy individuals who had no complaints of the hearing loss. The study of auditory function was performed using a clinical audiometer AC-40, manufactured by "Interacoustics" (Denmark). Studies of cerebral hemodynamics was performed with computer rheograph firm "DX-system." Results. Cerebral circulation of blood in the carotid (FM), and in vertebrobasilar (OM) systems were found in a qualitative assessment of the patients rheogram. This was confirmed by the analysis of quantitative indicators of workers REG. Significant (P